A systematic literature review of mobile applications to assist people with mild to moderate dementia in their daily lives / Zehang Cheng and Kamal Sabran - Zehang, Cheng; Sabran, Kamal (Universiti Teknologi MARA, 2023)
The popularity of smartphones has made mobile apps an essential tool for people in managing their daily lives. Helping people with dementia to make good use of mobile apps can reduce the stress on the patient's family and society. Mild and moderate dementia can be eliminated Mild and moderate dementia may be mitigated through simple teaching and human-centered design approaches that accommodate individuals with difficulty using mobile apps. This paper aims to identify the functionality and usability of mobile apps for people with dementia by reviewing mobile apps that assist people with mild to moderate dementia in their daily lives. The study searched the literature in five databases - Pubmed, Web of Science, SpringerLink, Taylor & Francis, and IEEE Xplore - and conducted a quality assessment. This review found that mobile applications to assist with daily living primarily support people with dementia with shopping and payment, location, image storage, medication reminders, and social interaction. A personalised user interface based on the profile and condition of the person with dementia can enhance usability. Preliminary findings suggest that mobile apps for people with dementia can address daily living needs, increase independence, and ease the stress of home care.